URGENSI MANAJEMEN DALAM PELAKSANAAN LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH - Tri Velyna (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2025)
In addition to misconceptions in guidance and counseling activities, problems also occur in guidance and counseling services in schools, related to the management of guidance and counseling, which is not yet optimal. This is illustrated based on phenomena that occur in schools, including lack of student needs analysis, unclear objectives of BK activities, absence of structured BK programs, high workload of BK teachers, limited facilities and infrastructure, lack of cooperation with subject teachers and parents, lack of BK teacher competence, irregular evaluation, absence of feedback mechanisms. The implementation of guidance and counseling programs in schools will not run smoothly without effective guidance and counseling management. This study aims to explain narratively the importance of management in implementing guidance and counseling services in schools. The approach in this study uses a qualitative approach with a type of library research. The results of the discussion show that the implementation of guidance and counseling services in schools needs to use the POAC management principle, which includes planning, organizing, actuating, and controlling, and the need for cooperation with all school stakeholders.